Possibilities of human emancipation: Teacher training courses in the department of human sciences at UFF - Lima, Cecilia Neves (Seven Editora, 2024)
This article aims to reflect on the original curricula of the pedagogy and field education courses of the Department of Human Sciences of the Fluminense Federal University, regarding the possibilities of social transformation and human emancipation that training can provide. Based on categories such as Critical multiculturalism (Mc Laren, 2000) and human formation (Freire, 2005), we seek to understand initial training in teacher training courses (pedagogy and rural education) as an instrument that contributes to the denaturalization of social representations linked to whiteness and the hegemony of scientific knowledge and as an instrument for the transformation of social reality. DOI:https://doi.org/10.56238/sevened2023.006-136